Functional characterization of CHEK2 variants in a Saccharomyces cerevisiae system - Delimitsou,A.; Fostira, F.; Kalfakakou,D.; Apostolou, P.; Konstantopoulou, I.; Kroupis, C.; Papavassiliou, A.G.; Kleibl,Z.; Stratikos,E.; Voutsinas, G.E.; Yannoukakos, D. (Hum.Mutat., 2019)
Genetic testing for cancer predisposition leads to the identification of a number of variants with uncertain significance. To some extent, variants of BRCA1/2 have been classified, in contrast to variants of other genes. CHEK2 is a typical example, in which a large number of variants of unknown clinical significance were identified and still remained unclassified. Herein, the CHEK2 variant assessment was performed through an in vivo, yeast-based, functional assay. In total, 120 germline CHEK2 missense variants, distributed along the protein sequence, and two large in-frame deletions were tested, originating from genetic test results in breast cancer families, or selected from the ClinVar database. Of these, 32 missense and two in-frame deletions behaved as non-functional, 73 as functional, and 15 as semi-functional, after comparing growth rates of each strain with positive and negative controls. The majority of non-functional variants were localized in the CHK2 kinase and forkhead-associated domains. In vivo results from the non-functional variants were in agreement with in silico predictions, and, where available, with strong breast cancer family history, to a great extent. The results of the largest, to date, yeast-based assay, evaluating CHEK2 variants, can complement and assist in the classification of rare CHEK2 variants with unclear clinical significance
Keywords: Alleles; Amino Acid Substitution; Checkpoint Kinase 2; Computational Biology; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; genetics; Greece; Humans; metabolism; methods; Models,Molecular; Mutation; Pedigree; Protein Conformation; Saccharomyces cerevisiae